Theodore Metochites' Sententious Notes Semeioseis gnomikai 61-70 & 72-81 - Wahlgren, Staffan (Kriterium, 2018)
"This volume contains a critical edition, with an English translation and notes, of 20 chapters of the Semeioseis gnomikai (""Sententious notes"") of the Byzantine statesman Theodore Metochites (1270-1332). The introduction gives an extensive, partly new, description and assessment of the manuscripts as physical objects and in their relationship to each other. The manuscripts discussed, and used in the edition, are the Par. gr. 2003 (P) and Marc. gr. 532 (M), both of the fourteenth century, and, wherever M is illegible, the Scor. gr. 248 (E), a sixteenth-century copy of M. In the edition, the reading of P (including the corrections by the main copyist, Michael Klostomalles, as well as a manus secunda) is generally adopted as the authoritative text. The volume concludes with a bibliography, an index of passages, and an index of names. The discussion in the essays touches upon several subjects, more or less related to each other. Among these are the ignorance of man and the difficulty to know anything, and the moral side of seeking an active life as opposed to ""living hidden""."